(untitled) (Orfeu, 2021)
The text presents a review of the book Francisco de Sá Noronha (1821-1881) - um músico português no espaço atlântico(CESEM/Editora Húmus, 2019), by Luísa Cymbron (Universidade Nova de Lisboa - CESEM), about the violinist and Portuguese composer born in Viana do Castelo in 1820 and died in Rio de Janeiro in 1881. As a composer of operas, operetas and other genres of vocal and instrumental music, Noronha was active in Portugal and Brazil in the 19th century, and his biography also includes trips to the United States, England and Cuba.